The Effects of Superovulation Prior to Mating and Zinc Supplementation on Milk Yields in Etawah-Grade Does - Adriani, Adriani; Sutama, IK; Sudono, A; Sutardi, T; Manalu, W (ANIMAL PRODUCTION, 2004)
Thirty six Etawah-grade does (BW ranged from 20.4 to 44.2 kg and age ranged from 2.5 to 7 years) were used to study the effects of superovulation prior to mating and zinc supplementation on milk yields. The experimental does were assigned into a randomized block design with a 2 x 3 factorial arrangement. The first factor was PMSG (pregnant mare serum gonadotrophin) injection with 2 levels (0 IU/kg BW [nonsuperovulationâNSO] and 15 IU/kg BW [SuperovulationâSO]). The second factor was zinc concentration in the diet with 3 levels (40 mg/kg DM [Z-40], 60 mg/kg DM [Z-60], and 80 mg/kg DM [Z-80]). Intravaginal sponge (60 mg medroxyprogesterone acetate) was applied for 14 days to synchronize estrus cycle. Twenty fourÂ  hours prior to sponge removal, PMSG was injectedÂ  toÂ  stimulate superovulation. AfterÂ  sponge removal,Â  5 experimental doesÂ  were mixed with 1 buck for natural mating. DuringÂ  pregnancyÂ  the experimental does were fed andÂ  raised inÂ Â  individual stables. Udder volumeÂ  was measured every other week from weeks 12 to 21 ofÂ  pregnancy.Â  During lactationÂ  (one week toÂ  5 months post partum) kids were separated from the does, andÂ Â  milk was harvested by hand milking. Milk samples were taken every other week for determination of milk quality. The resultsÂ  indicated thatÂ  superovulation increased udder differential growthÂ  by 80% (822.85 vs 1481.25 cm3/head), milk yield byÂ  32% (567.14 vs 746.52 g/head/day).Â  Zinc concentrationÂ  increased udder differential growth and milk yield. Milk productions for does receiving 40, 60 and 80 mg/kg DM were 565.68, 737.88 and 666.92 g/day, respectively.It was concluded thatÂ  superovulation and zinc supplementationÂ  increased milkÂ  yield in Etawah Grade does. (Animal Production 6(2): 86-94 (2004)Â Key Words: Â Superovulation, Zinc, MilkÂ  Yield, Etawah-Grade